5 Foundation doctor fellowship in simulation: a valuable yet currently unique position. (17th November 2016) - Williams, R; McIndoe, A; Grant, D
Abstract : From December 2015 to April 2016, I worked as the 'Foundation Simulation Fellow' in the Bristol Medical Simulation Centre (BMSC). Although the fellowship has been running for several years as part of the Severn Deanery Foundation School Programme, to the best of our knowledge there have not been any similar positions created for foundation doctors practising elsewhere in the UK. In addition to providing support as faculty in courses run at the BMSC, the foundation fellow is a valuable member of the point-of-care team running multidisciplinary simulation scenarios throughout our affiliated hospitals, and independently runs simulation programmes for medical students. Unlike in other teaching fellow posts, the simulation fellowship provides invaluable experience in writing scenarios, delivering teaching, and providing feedback in an appropriate manner to delegates of differing professional backgrounds and seniority. Exposure to simulated medical emergencies whilst helping on simulation courses designed for senior delegates has much improved my understanding of the management of such conditions. Identification of system errors unearthed through point-of-care simulation has led to several quality improvement projects. I hope to continue to develop the skills acquired during my time at BMSC to contribute to simulation training in other institutions in future. Simulation is an exciting, relatively novel method of medical education that is continually evolving. More of our most junior doctors working in front-line services should be given the opportunity to develop the skills to become simulation trainers in order to cultivate future innovation in the field. I hope that this poster presentation will both encourage foundation doctors and medical students to pursue an interest in medical simulation, and provide evidence to those in a position to create further positions for foundation trainees that it would be worthwhile.